Model Praktik Pendidikan Anti Perundungan di Lembaga PAUD: Implementasi pada TK Cut Meutia dan TK ABA Batoh Banda Aceh - Fitrah Nabila Dista; Qonita Luthfiah; Aulia Wahyunisa; Ova Lativa; Irma Surianti; Ratna Fitri (Early Stage, 2026)
Bullying in early childhood constitutes a serious threat to children’s socio-emotional development and to the creation of a safe learning environment. However, anti-bullying education practices in Indonesian early childhood education institutions remain largely partial and have yet to adopt an integrated practice model that has been empirically tested in the field. This study developed and implemented the Anti-Bullying Education Practice Model (MPPAP) using an Educational Design Research (EDR) approach through four stages: preliminary study, model design and expert validation, field implementation, and reflection and refinement. The implementation was conducted over one month in 12 sessions, involving 6 teachers and 40 children in Group B aged 5–6 years from TK Cut Meutia and TK Aisyiyah Bustanul Athfal (ABA) Batoh Banda Aceh. Data were collected through observation, semi-structured interviews, documentation, and reflective notes, and were analyzed using Miles and Huberman’s interactive model. Data trustworthiness was ensured through source and technique triangulation. The model was validated through expert judgment by an early childhood education expert and was declared feasible for implementation with minor revisions before being applied in the field. The findings indicate that MPPAP consists of five integrated components: strengthening anti-bullying awareness, social-emotional learning, participatory learning, partnership-based prevention, and restorative response. The implementation of the model improved children’s ability to recognize emotions, demonstrate prosocial behavior, and resolve conflicts peacefully; reduced behaviors such as mocking and excluding peers; strengthened teachers’ sensitivity; increased parental involvement; and fostered a safer and more inclusive learning environment. Compared with social-emotional learning programs, parenting interventions, or partial anti-bullying strategies,MPPAP offers an integrated framework that has been directly tested in the field, thereby providing both theoretical and practical contributions to anti-bullying education in early childhood education settings